RANCANG BANGUN MULTIMEDIA INTERAKTIF BELA DIRI MODERN DENGAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE - Aziz Fandika Pamungkas; Ba Ramadhan, Ayzuar; Tri Purnomo, Juli (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
The development of interactive learning media requires appropriate software methods because effective and efficient use of multimedia really supports learning. The lack of interesting and interactive learning media is a major problem because most people, especially beginners in martial arts, will not know how to use certain techniques needed to learn self-defense. Interactive media is the best way to overcome this problem. This research aims to create an interactive multimedia learning resource that provides interesting information about contemporary martial arts, especially for martial arts fans. Text, audio, images, and video are the content sources of this system. To develop this interactive multimedia with the Life Cycle of Multimedia Development (MDLC). The test results show that interactive multimedia is very suitable to be used as a medium for information about modern martial arts.